Socio-economic Attributes and Training Needs of Apple Growers of Kashmir Valley - Tantray, Abdul Majid; Ram, D.; Jahan, Nasreen (Indian Journal of Extension Education, 2010)
The study is based on the inferences of 142 sampled participants collected during Extension Education Week Celebrations of the University and revealed an increasing trend in the land use pattern for fruit cultivation. Among the sampled population 42.3 percent considered fruit cultivation as their main activity followed by crop production, vegetable cultivation and other agricultural activities respectively. In temperate fruit cultivation, almost all have preferred apple cultivation for obvious reasons of somewhat better shelf Iife and marketing than the other fruits. To boost the apple production at farmer's level and make viable and income generating activity, training needs were assessed, ranked and categorized as per the perceptions of the growers for future programmes and successful ventures. The most essential group of training needs in apple cultivation perceived by the growers were about apple cultivars/varieties, plant protection (lPM), manuring and Fertilization (INM), marketing of fruits, pruning and training, pre-harvest drops and availability of quality inputs respectively than other aspects, The highest total score of 361 with mean score of 2.54 was obtained for the apple cultivars I varieties and lowest total score of 192 with 1.35 mean score for apple orchard layout. The 'Essential' group of training needs obtained at total score of 313 with 2.20 mean score.